Competitive Advantage of Green Hospitality Business Practices in 5 Star Hotels in Bali - Budarma, I Ketut; Astawa, I Ketut; Widhari, Cokorda Istri Sri; Erawati, Ni Made Rai (Technium Social Sciences Journal, 2020)
This study gives an advantages account of green hospitality business practices in 5-star hotels in Bali island. The methods used were focus group discussion, case study, direct observation, and questionnaire. The results showed that all the studied hotels have practiced green hospitality, and have successfully integrated local values system pertaining to culture and ecology as green vision to elevate their social and ecological marketing. Furthermore, their green hospitality practices have been locally and internationally certified and recognized, making the hotels known for green products. These made them to be in demand because most clients are looking for green hotels that preserve culture and nature. Also, green practices have changed the image of hotels to be ecologically and socio-culturally friendly, and as agents of local economy development. In addition, the practices have made the hotels capable of producing products and services with lower costs, and higher profit to compete in a global market to sustain their competitive advantages.